PENGELOLAAN KEUANGAN NEGARA BERBASIS APLIKASI â€œSAKTIâ€ DI KANTOR PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNANPROVINSI BALI - I Gusti Ngurah Dharma Astawa; I Made Yudhiantara; I Gede Agus Wibawa (JOURNAL AKSES STIA MALANG, 2023)
The development of information and communication technology has become a global trend today,including the digitalization of the government sector, which is better known as electronic government(E-Government) or Electronic-Based Government Systems (SPBE). SPBE developmentby a governmentinstitution aims to improve information and service connectivity quickly and efficiently, not only betweeninstitutions but also with the public as users of public services. The year 2022 is the beginningimplementation of SAKTI Full Module namely the Institutional Level Financial Application System forthe APBN Management Work Unit, with integrated database, including including the Financial andDevelopment Supervisory Board (BPKP). This study seeks to examine the application of SAKTI inmanaging state finances, and to find out whether system quality,information quality, and service qualitysupport user satisfaction, individual performance, and provide benefits to the organization. This studyused a qualitative method, by conducting interviewswith employees, focus group discussion,literaturestudy and document review, and observing the implementation of SAKTI for the 2022 fiscal year at theBali Province BPKP Representative Office.The results showed that system quality, information quality,and service quality very well support state financial management from the budgeting stage, budgetexecution, to financial reporting. Thesuggestions given included improving SAKTI's performance suchas updating application features, validation mechanisms, increasing SAKTI's server capacity andincreasing the competence of financial managers through integrated training.